JUDICIAL ACTIVISM IN INDONESIA CONSTITUTIONAL COURT: The Adjudication of Regional Election Disputes - Diar, Adithiya; Saputra, Beny (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
In resolving disputes over regional head election results, the Constitutional Court often takes legal steps by postponing the application of the vote margin threshold. In addition, the Court makes judicial reasoning to harmonize various interpretations among election organizers. This study aims to identify the reasons for the deferment of the threshold application and to examine the Constitutional Court's judicial reasoning in handling this dispute. Using normative legal research methods with a conceptual, statutory, and case-based approach, this study concludes that the Constitutional Court has set aside the vote margin threshold in extraordinary cases, particularly in cases involving procedural violations or candidates' ineligibility to advance as participants. This is evident in election disputes from 2016 to 2025. Another conclusion is that the Constitutional Court's use of judicial reasoning aims to resolve legal ambiguity and prevent inconsistencies in the application of election norms among stakeholders. The findings of this study carry significant strategic implications for both election organisers and lawmakers. This study contributes to the understanding of how the Constitutional Court's judicial activism shapes electoral justice and the need for legislative harmonization.